Saint Menas in Medieval Georgia - Aleksidze, Nikoloz (Vox Patrum, 2025)
Despite the survival of St Menas’s hagiography in various Georgian iterations and his commemoration in practically all Georgian calendars and martyrologies – both pre- Constantinopolitan and Byzantine – the cult of St Menas was weak in Georgia. To this day, collections of St Menas’s miracles in Georgian await discovery, apart from one miracle discussed near the end of my article. Nonetheless, given the significant role Georgian evidence plays in the study of late antique and mediaeval hagiography and the cult of saints, the article attempts to contextualise the cult of St Menas from the Georgian perspective.